PENDIDIKAN KELUARGA DALAM PENGUATAN LITERASI DASAR PADA ANAK - Woro Wuryani; Via Nugraha (STKIP Siliwangi, 2021)
This study is motivated by the low basic literacy problem of children. Based on news from Republika (Darma, 2020) states that the ability to process information through literacy or literacy culture in Indonesian society is very low. Chairman of the Indonesian Literacy Culture Development Forum Satria Darma said, based on research results from international institutions, the literacy culture of the Indonesian people is very low compared to other countries in the world. The reading position of Indonesian students ranks 57th out of the 65 countries studied (PISA).